(untitled) (Studia theodisca, 2016)
The atomic play Atom vor Christus (1952) by the Viennese playwright Kurt Becsi (1920-1988) is one of the very numerous works on the subject of the nuclear threat that appeared in German-speaking countries in the 1950s and ’60s. This article investigates the complex Christian religious discourse that embeds the dramatization of atomic issues and apocalyptic ideas of the End in Becsi’s play. Special focus is given to such aspects as the struggle between generations and, in particular, the conflict between the unscrupulous scientist (and his hubris) and the figure of the repentant bomber pilot that becomes a monk (Science versus love, logic versus Christian grace).